Marijuana use and its correlates among school-going Jamaican adolescents: a finding from a national survey - Dadras, Omid (Frontiers in Psychiatry, 2024)
Introduction: The latest data indicate almost a fifth of Jamaican adolescents used marijuana in the past 30 days. To ensure the optimal allocation of resources, a country-specific understanding of factors associated with marijuana use among adolescents is essential. Therefore, this study aimed to address this gap among adolescents aged 13-17 in Jamaica. Methods: We analyzed data from the latest Jamaica Global School-Based Student Health Survey conducted in 2017. The sample consists of school-going Jamaican adolescents in 7th- 12th grades. The prevalence of recent marijuana use was assessed and compared across different demographics, substance use, and risk behaviors using bivariate and multivariable logistic regression. Results: Older adolescents and males had a higher likelihood of recent marijuana use. Psychosocial risks such as loneliness, frequent worry, suicidal ideation, physical attacks, and school absenteeism were associated with higher marijuana usage. Parental smoking increased the odds, but strong parental support and awareness decreased it. Other substance uses, especially amphetamine and tobacco products, had strong associations with marijuana use. Early initiation of substances was associated with a higher risk of marijuana use. Sexually active adolescents, especially those initiated before age 14, had higher marijuana use rates. Conclusion: The intricate link between harmful and supportive psychosomatic and risk behaviors with recent marijuana use underscores the importance of holistic interventions and policies focusing on emotional health, parental guidance, substance education, and sexual activity implications.